Electroencephalogram (EEG) pattern for human smoke habit - Mokhtar, A. S.; Fuad, N.; Marwan, M. E.; Norazlin, Norazlin (Penerbit UTHM, 2022)
The brain is most important part of the human body. Smoking cigarettes is a bad habit, however the total numbers of smokers continue developing. Most smokers give 'to release stress and bored' as a purpose behind smoking. Under this circumstance, the interested of brain condition for smoke affinity are useful for varies biomedical field. The essential motivation behind this research is to investigate the Electroencephalogram (EEG) pattern for smoker using sub-band of theta, alpha and beta groups focus on Power Spectral Density (PSD). EMOTIV Pure•EEG™, SPSS and Excel is used as the software while Emotiv Insight is used as the hardware in this research. 5 smokers and 5 non-smokers were tested for this exploration. EEG data was recorded for 5 minutes. Results demonstrated that smokers have lesser theta band which shows a less stressed on feeling as contrasted with non-smokers with a higher theta band. Smokers additionally higher alpha band which shows that they are more casual contrasted with non-smokers with lower alpha band. In any case, smokers are lower beta band that shows they are lesscognizant contrasted with non-smokers. Recently, electronic cigarettes (ecigarette) have been proposed as a successful instrument for smoking restraint.